(570) Economic Criteria for Foreign Loans المعايير الاقتصادية للقروض الأجنبية - A. Qayoum (معهد التخطيط القومى, 2024)
The main bottleneck in the development of underdeveloped countries is the storage of capital including human capital, technical and managerial skill and entrepreneurial ability. Left of themselves, their rate of development will be very slow depending of success with which this storage is reduce.